APLIKASI MEDIA EDUKASI INTERAKTIF BERBASIS AUGMENTED REALITY - Ibrahim Ibrahim (Jurnal Teknovasi : Jurnal Teknik dan Inovasi, 2021)
The Education model is widely applied using various technologies and tools that support it, either the most traditional or the modern ones such as books, articles, tutorials and internet CDs. In terms of reading education among preschoolers, children often have difficulty to understand the meaning of the word read to the object in question. Augmented Reality in educational media that is interactive aims to facilitate in understanding words those have been given. In this research, designed an application that allows users in this case pre-school students interact with interfaces to interpret the meaning of the writings provided in the form of props so that pre-school students can directly see the object in a real time. The application requires both internal and external webcam cameras as input source, then this app will detect marker by using tracking system on ARToolkit software, then the object will appear above the marker as directed.